Artificial Intelligence in science and everyday life, its application and development prospects - Słapczyński, Tomasz (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
Abstract— The main purpose of the article is to determine the impact of artificial intelligence on society and industry. What role the development of this technology will play on the economy and society in the future. The question should be asked: how will artificial intelligence affect society and what will be the effects of its increasingly widespread use and whether it poses any threats. The main methods used in the article are the analysis of scientific literature, synthesis of collected facts and knowledge obtained from official data, e.g. documentation of programming languages. The main conclusions from the paper is the growing importance of AI for society and its development, which will affect into various areas of life.